Thirst-guided participant-controlled intravenous fluid rehydration: a single blind, randomised crossover study. (April 2020) - Lacey, Jonathan; Corbett, Jo; Shepherd, Ant; Dubois, Andre; Hughes, Fintan; White, Danny; Tipton, Mike; Mythen, Michael; Montgomery, Hugh
Abstract: Background: Dehydration is common in hospitals and is associated with increased mortality and morbidity. Clinical assessment and diagnostic measures of dehydration are unreliable. We sought to investigate the novel concept that individuals might control their own intravenous rehydration, guided by thirst. Methods: We performed a single-blind, counterbalanced, randomised cross-over trial. Ten healthy male volunteers of mean age 26 (standard deviation [sd ] 10.5) yr were dehydrated by 3–5% of their baseline body mass via exercising in the heat (35°C, 60% humidity). This was followed by a 4 h participant-controlled intravenous rehydration: individuals triggered up to six fluid boluses (4% dextrose in 0.18% sodium chloride) per hour in response to thirst. Participants undertook two blinded rehydration protocols which differed only by bolus volume: 50 ml (low volume [LV]) or 200 ml (high volume [HV]). Each hour during the rehydration phase, plasma osmolality (pOsm) was measured and thirst score recorded. Nude body mass was measured at baseline, after dehydration, and after the rehydration phase. Results: In both conditions, the mean dehydration-related body mass loss was 3.9%. Thirst score was strongly associated with pOsm (within-subject r =0.74) and demand for fluid decreased as pOsm corrected. In the HV condition, participants rapidly rehydrated themselves (mean fluid delivered 3060 vs 981 ml in the LV condition) to body mass and pOsm no different to their euhydrated state. Conclusion: Healthy individuals appear able to rely on thirst to manage intravenous fluid intake. Future work must now focus on whether patient-controlled intravenous fluids could represent a paradigm shift in the management of hydration in the clinical setting. Clinical trial registration: NCT03932890